Impacts of in-kind transfers on household food consumption: evidence from targeted food programmes in Bangladesh - del Ninno, Carlo; Dorosh, Paul A. (Informa UK Limited, 2003)
This article examines the impact of wheat transfers and cash incomes on wheat consumption and wheat markets. Using propensity score matching techniques, the MPC for wheat is on average 0.33, ranging form essentially zero for Food For Work (a programme with large transfers) to 0.51 for Food For Education. Econometric estimates indicate that the total marginal propensity to consume (MPC) wheat out of small wheat transfers to poor households is approximately 0.25, while MPCs for wheat out of cash income are near zero. This increase in demand for wheat reduces the potential price effect of the three major targeted programmes by about one-third." -- Authors' Abstract